Кримінальне судочинство щодо неповнолітніх осіб та виконання покарань: історико-правовий аналіз (друга половина ХІХ-початок ХХ століття) - Стороженко, І. О.; Storozhenko, I. O. (Юридична наука. - 2019. - № 12 (102), т. 1. - С. 314-319, 2019)
Досліджено кримінальне судочинство неповнолітніх осіб та виконання покарань на прикладі другої половини XІХ- початку ХХ століття через історико-правовий аналіз. Констатовано, що профілактична робота зі злочинністю та бездоглядністю неповнолітніх, яка вживалась наприкінці XIX століття, практично не мала результатів. Незначна кількість установ і недостатність заходів по боротьбі з жебрацтвом та бродяжництвом, як соціальним явищем, не вирішувало проблеми експлуатації дітей та підлітків, їх втягнення у злочинну діяльність по вилученню доходів, здобутих незаконним шляхом. Розглядаючи кримінальне законодавство в історичному аспекті, відзначено, що воно на більшості етапів свого розвитку шукало шляхи виправлення юних правопорушників, не пов’язані із застосуванням заходів кримінальної репресії.

The scientific article is devoted to the study of criminal proceedings of minors and the execution of sentences on the example of the second half of the 19th - early 20th centuries through historical and legal analysis. Taking into account the doctrinal study, it was stated that preventive work with crime and neglect of minors, which was taken at the end of the 19th century, had practically no results. The small number of institutions and insufficient measures to combat begging and vagrancy, as a social phenomenon, did not solve the problem of the exploitation of children and adolescents, their involvement in criminal activities to seize the proceeds of illegally obtained. Until the beginning of the 20th century, almost all prisons operated prison community committees, and guardians collected donations for prisons and controlled prison authorities in order to detect theft and bribery. Studying the provisions of the criminal legislation of the second half of the 19th century - the beginning of the 20th century, one cannot but note the tendency to humanize it, aimed at correcting minors and minors who violated the boundaries of the law, introducing them to work and applying measures that contribute to their social adaptation. In the historical context of criminal law, it has sought, at most stages of its development, ways of correcting young offenders that do not involve the use of criminal repression. Attention was drawn to the fact that during the period under study, European criminal legislation was actively being reformed, criminal codes in force until the middle of the 19th century were being revised, this process also affected the domestic judicial system: a public and public hearing of cases was being introduced, the institution of a jury court was being established, special courts were being established to hear cases against minors, the network of correctional institutions and the like was being expanded. For the legislation of the Russian Empire, which had no experience in creating special children’s courts, such a practice was a novelty, so legislators went on the path of using in criminal law the already proven experience in juvenile justice, which was used in European countries.

Исследовано уголовное судопроизводство несовершеннолетних лиц и исполнение наказаний на примере второй половины XIX-начала ХХ века через историко-правовой анализ. Констатировано, что профилактическая работа с преступностью и безнадзорностью несовершеннолетних, которая применялась в конце XIX века, практически не имела результатов. Незначительное количество учреждений и недостаточность мер по борьбе с попрошайничеством и бродяжничеством, как социальным явлением, не решало проблемы эксплуатации детей и подростков, их вовлечение в преступную деятельность по изъятию доходов, полученных незаконным путем. Рассматривая уголовное законодательство в историческом аспекте, отмечено, что на большинстве этапов своего развития оно искало пути исправления юных правонарушителей, не связанные с применением мер уголовной репрессии.
Criminal judiciary against juveniles and implementation of penalties: historical and legal analysis (second half of XIX-early XX century)
Стороженко, І. О. Кримінальне судочинство щодо неповнолітніх осіб та виконання покарань: історико-правовий аналіз (друга половина ХІХ-початок ХХ століття) / Стороженко І. О. // Юридична наука. - 2019. - № 12 (102), т. 1. - С. 314-319.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; Кримінологія. Criminology. Криминология; Кримінальне право. Criminal Law. Уголовное право; Кримінально-виконавче право. Criminal and Executive Law. Уголовно-исполнительное право; неповнолітні; minors; несовершеннолетние; кримінальна відповідальність; criminal liability; уголовная ответственность; протидія злочинності; crime prevention; противодействие преступности